(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the role of digital tools in enhancing foreign language skills among learners with special educational needs (SEN) in home-based instructional settings. Employing the IMRAD (Introduction, Materials and Methods, Results, and Discussion) research framework, the study conducts a mixed-methods systematic review of 72 peer-reviewed studies published between 2014 and 2025. The investigation addresses four core research questions concerning the types of digital tools employed, their effectiveness across receptive and productive language skills, the factors mediating successful implementation, and the barriers confronting families and educators. Results reveal that digital tools including mobile applications, gamified platforms, speech recognition software, augmentative and alternative communication (AAC) technologies, virtual reality environments, and AI-powered adaptive tutoring systems demonstrate statistically significant positive effects on vocabulary acquisition, reading comprehension, listening skills, and oral communication for learners with diverse disabilities. However, effectiveness is mediated by variables including disability type and severity, the quality of caregiver scaffolding, technological accessibility features, and the alignment between tool design and individual learner profiles. The discussion situates these findings within Universal Design for Learning (UDL) and sociocultural theoretical frameworks, identifies critical gaps in the evidence base, and proposes recommendations for practitioners, developers, and policymakers committed to equitable foreign language education for all learners.